RFID for the Supply Chain and Operations Professional - Zelbst, Pamela (Business Expert Press, 2012)
Ebook from IG Library ; The quality and effectiveness of decisions made within an organization and its supply chain depend on the accuracy and timeliness of the information on which they are based. Radio frequency identification (RFID) is a technology that can provide more accurate information in near real time and thus increase the quality and timeliness of decisions based on that information. RFID systems are currently in use in areas such as inventory management, process control, asset tracking and monitoring, and retail point of sale. Organizations that appropriately incorporate RFID into their operations and information management systems have increased their agility, effectiveness, and efficiency, resulting in organizational growth and increased profitability.